Nursing diagnoses of newborns with sepsis in a Neonatal Intensive Care Unit - Ana Paula de Souza Santos; Maria de Lourdes Costa da Silva; Nilba Lima de Souza; Gabriela Miranda Mota; Débora Feitosa de França (Universidade de São Paulo, 2014)
OBJECTIVES: to elaborate the Nursing Diagnoses of newborns with sepsis in a neonatal intensive care unit and characterize the profile of the neonates and their mothers.METHOD: a cross-sectional and quantitative study, with a sample of 41 neonates. A physical examination and consultation of the hospital records were undertaken, using an instrument. The elaboration of the Nursing Diagnoses followed a process of diagnostic inference and was based on the North American Nursing Diagnosis Association 2012-2014.RESULTS: the mothers were around 25 years old, had a low average number of pre-natal consultations, and various complications during the pregnancy; and the newborns were predominantly premature and with very low birth weights. Five Nursing Diagnoses predominated, and all the neonates presented Risk of Shock and Risk of fluid volume imbalance.CONCLUSION: the Nursing Diagnoses of the neonates with sepsis can guide the formulating of specific assistential plans. The study contributes to the generation of new knowledge and found various relationships between the Nursing Diagnoses and the variables selected in the characterization of the neonates, which deserve to be elucidated in greater detail based on further research on the issue.